2017
DOI: 10.1097/sla.0000000000002407
|View full text |Cite
|
Sign up to set email alerts
|

Individualized Metabolic Surgery Score

Abstract: This is the largest reported cohort (n = 900) with long-term postoperative glycemic follow-up, which, for the first time, categorizes T2DM into 3 validated severity stages for evidence-based procedure selection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
2
11

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(92 citation statements)
references
References 36 publications
2
77
2
11
Order By: Relevance
“…Aminian et al38 devised the individualized metabolic surgery (IMS) scoring system to guide procedure selection based on long-term (>5 years) glucose control in patients with T2DM. They retrospectively collected data from 659 T2DM patients who underwent RYGB or SG at a single center in the United States and had completely documented glycemic follow-up for at least 5 years after surgery.…”
Section: Prediction Models Of Diabetes Remissionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aminian et al38 devised the individualized metabolic surgery (IMS) scoring system to guide procedure selection based on long-term (>5 years) glucose control in patients with T2DM. They retrospectively collected data from 659 T2DM patients who underwent RYGB or SG at a single center in the United States and had completely documented glycemic follow-up for at least 5 years after surgery.…”
Section: Prediction Models Of Diabetes Remissionmentioning
confidence: 99%
“…Preop, preoperative; HbA1c, glycosylated hemoglobin; RYGB, Roux-en-Y gastric bypass; SG, sleeve gastrectomy. Adapted from Aminian A, et al Ann Surg 2017;266:650–7, with permission from Wolters Kluwer Health Inc 38…”
Section: Figurementioning
confidence: 99%
“…Recently, bariatric surgery is endorsed as a treatment for obese diabetic patients by the International Diabetes Federation, American Diabetes Association (ADA), and American College of Surgeons [23]. However, T2DM remission rates appear to differ between surgery procedures, where RYGB has higher rates compared to SG and Gastric Band [4,24]. A study reported 60.2% of RYGB patients achieved diabetes remission after 7 years of surgery, compared to 20.3% for Gastric Banding [4].…”
Section: Introductionmentioning
confidence: 99%
“…A study reported 60.2% of RYGB patients achieved diabetes remission after 7 years of surgery, compared to 20.3% for Gastric Banding [4]. Long-term diabetes remission for SG was quite low in two studies: 35.3% for Taiwanese patients and 28% for American patients after 5 years of surgery [13,24], but another study reported a remission rate of 66% five years after SG [25].…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that the SOS study contains a high proportion of patients with screen-detected T2D, resulting in a low average T2D duration, which may explain why addition of T2D duration to the 2-year weight change model did not increase the discriminatory capacity. However, the difference in T2D duration in non-relapse (00.4 and 0.3 years, respectively) and relapse (1.1 and 0.9 years, respectively) groups at 10 and 15 years confirms the importance of early surgical intervention for long-term glycemic control [ 2 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%